South Asia Is Far from Achieving Universal Coverage of Essential Nutrition Interventions: Examining Coverage, Trends, and Inequities, 2005 to 2018. (29th May 2020) - Singh, Nishmeet; Nguyen, Phuong; Scott, Samuel; Kim, Sunny; Neupane, Sumanta; Murira, Zivai; Heidkamp, Rebecca; Bhutta, Zulfiqar; Menon, Purnima; Torlesse, Harriet
Abstract: Objectives: South Asia carries the largest burden of malnutrition globally. Tracking coverage of nutrition interventions is a critical step in designing effective nutrition policies and monitoring progress in the region. This paper examines coverage, trends, and inequities in nutrition interventions in South Asia. Methods: Data were from Demographic and Health Surveys in Afghanistan (2015), Bangladesh (2011, 2014), India (2006, 2015), Maldives (2009, 2017), Nepal (2011, 2016) and Pakistan (2013, 2018). We examined essential interventions spanning the continuum of care: 2 in the pre-conception period, 7 in pregnancy, 4 in postpartum and 9 in childhood. We calculated absolute changes, average annual change rates, and concentration indices to examine trends and inequalities in coverage and composite coverage index (CCI) over time by residence and wealth quintiles. Results: Coverage of nutrition interventions has generally improved since 2005 but coverage levels remain low and varied. Improvements have occurred for consumption of iodized salt, institutional births, antenatal care, weight monitoring during pregnancy, zinc and ORS supplementation (16 to 34 percentage points, pp). However, coverage of some child-level interventions has decreased: full immunization, preventive deworming, vitamin A supplementation and postnatal care (−9 to −13 pp). Median regional coverage was below 75% for 17 of 22 interventions. Extremely low coverage persists for preventive deworming during pregnancy (10%) and daily Iron supplementation for children (5%), while high coverage (>80%) exists for consumption of iodized salt, attendance by a trained provider during pregnancy and weight monitoring during pregnancy. Large coverage gaps were found for CCI by wealth (10–45pp higher in rich, except Maldives) and residence (3–22pp higher in urban), with the gap decreasing over time in most countries. Conclusions: Despite improvements in nutrition intervention coverage since 2005, universal coverage is still far from optimal and unequally affects poor, rural women and children in South Asia. More work is needed to close coverage gaps and measure the quality of nutrition interventions. Funding Sources: BMGF through DataDENT.